Inventory of the Superfamily of P-Type Ion Pumps in Arabidopsis - Axelsen, Kristian B. (American Society of Plant Physiologists, 2001)
A total of 45 genes encoding for P-type ATPases have been identified in the complete genome sequence of Arabidopsis. Thus, this plant harbors a primary transport capability not seen in any other eukaryotic organism sequenced so far. The sequences group in all five subfamilies of P-type ATPases. The most prominent subfamilies are P(1B) ATPases (heavy metal pumps; seven members), P(2A) and P(2B) ATPases (Ca(2+) pumps; 14 in total), P(3A) ATPases (plasma membrane H(+) pumps; 12 members including a truncated pump, which might represent a pseudogene or an ATPase-like protein with an alternative function), and P(4) ATPases (12 members). P(4) ATPases have been implicated in aminophosholipid flipping but it is not known whether this is a direct or an indirect effect of pump activity. Despite this apparent plethora of pumps, Arabidopsis appears to be lacking Na(+) pumps and secretory pathway (PMR1-like) Ca(2+)-ATPases. A cluster of Arabidopsis heavy metal pumps resembles bacterial Zn(2+)/Co(2+)/Cd(2+)/Pb(2+) transporters. Two members of the cluster have extended C termini containing putative heavy metal binding motifs. The complete inventory of P-type ATPases in Arabidopsis is an important starting point for reverse genetic and physiological approaches aiming at elucidating the biological significance of these pumps.